Technological perspectives for utilisation of waste glycerol for the production of biofuels: A review - Chilakamarry, Chaitanya Reddy; Mimi Sakinah, A. M.; Zularisam, A. W.; Pandey, Ashok; N. Vo, Dai-Viet (Elsevier, 2021)
The depletion of fossil fuel reserves and the ever-increasing demand for energy due to growing industries, rapid population growth, and increasing concerns about environmental pollution have led to the exploration of green and alternative fuels. Bioethanol is one of the most promising biofuels and a key factor in shifting the transportation sector’s dependence from petroleum-based sources to renewable and sustainable energy sources. This review highlights the development of bioethanol from first to third-generation. First-generation sources include food crops, second-generation sources include feedstocks from agricultural residues, municipal waste or forestry waste, and third-generation sources include algal biomass to produce bioethanol for commercial scale in world are emphasised. Various methods such as pre-treatment, hydrolysis by acid and enzymes, fermentation to produce bioethanol, and distillation a separation processes to obtain anhydrous ethanol are described. Current advances in using biodiesel industrial by-product crude glycerol waste as the best alternative, renewable and sustainable source for ethanol production in the circular economy are also presented. The significant role of crude glycerol in various applications and the conversion of glycerol to ethanol are focused. In addition, the challenges and opportunities for future work are highlighted. The potential application of bioethanol as a biofuel to reduce environmental impact for a clean and sustainable future is described